Tingkat Kepuasan Nasabah Terhadap Kualitas Layanan Perbankan Syariah di Yogyakarta - Cahyani, Putri Dwi (Esensi: Jurnal Bisnis dan Manajemen, 2016)
The Customer Satisfaction to Islamic Banking Service Quality in YogyakartaThe Objective Of The Present Study Was To Find Out Service Quality's Factors that influences for customer satisfaction, the obtrusive criteria that affect customer satisfaction and analyze the level of customer satisfaction in each Islamic bank in Yogyakarta based adaptation CARTER models.  CARTER is model based on SERVQUAL dimensions in addition with new dimension called “Compliance with Islamic law” which is suitable for the Islamic banking industry.  Research was conducted by distributing questionnaires to 200 customers consisting of four Islamic banking in Yogyakarta. The analysis method used Structural Equation Model (SEM). The conclusions from this study regarding customer satisfaction about service quality in islamic banks has been above the moderate (high enough). The Factors that give big effect for customer's satisfaction in islamic banking are responsiveness, compliance , and empathy. With analysis of variance was concluded that the quality of every Islamic banks do not have significant differencesDOI: 10.15408/ess.v6i2.3570